2002
DOI: 10.1108/03068290210417098
|View full text |Cite
|
Sign up to set email alerts
|

Chinese cultural values and the Asian meltdown

Abstract: Despite the continuing interest in a concern for relationships between culture, management values and economic activity, there is a lack of empirical evidence about these relationships during the unprecedented economic transformations in Asian nations in the 1990s. This study evaluated variations in values that tapped concerns fundamental to the Chinese world view during the period of the Asian financial crisis of 1997. Data were provided by ethnic Chinese managers from Hong Kong, Malaysia and Singapore prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The findings and implications were concluded as follows: First, the culture comparison among Chinese in China, Chinese in Japan and Japanese indicated that there is significant difference among three groups on culture dimensions, as well as, the culture dimensions between two Chinese groups don't have significant differences, but both of them have significant differences with Japanese. The result confirms that although the environment will influence culture and globalization has been radically taking place all over the world, each national culture still owns its uniqueness for its particular core value [6], and the core value of culture would be relatively stable even in the face of substantial change and turbulence [9].…”
Section: A Conclusionsupporting
confidence: 54%
See 1 more Smart Citation
“…The findings and implications were concluded as follows: First, the culture comparison among Chinese in China, Chinese in Japan and Japanese indicated that there is significant difference among three groups on culture dimensions, as well as, the culture dimensions between two Chinese groups don't have significant differences, but both of them have significant differences with Japanese. The result confirms that although the environment will influence culture and globalization has been radically taking place all over the world, each national culture still owns its uniqueness for its particular core value [6], and the core value of culture would be relatively stable even in the face of substantial change and turbulence [9].…”
Section: A Conclusionsupporting
confidence: 54%
“…Some researchers pointed out culture are relatively stable even in the face of substantial change and turbulence [9], while, other researchers indicated culture may transcend national borders, compared with the cultural effects, the national effect is more influential [10]. Since there is little empirical work to investigate the culture difference between Chinese people at home and abroad, thus, this research is not only to demonstrate the cultural diversity between Chinese and Japanese, but also discuss the relationship between Chinese in China and Chinese in Japan.…”
Section: Literature and Research Hypothesesmentioning
confidence: 99%
“…Objective or actual firm performance was not measured; instead, items on perceived performance were included in the scale. Perceived performance yields more merits as most owners of small and medium enterprises (SMEs) are reluctant to reveal their actual performance (Ward, Pearson & Entrekin, 2002). Perceived performance is able to provide the researcher a full picture of the firm's performance as in the case of actual performance (Delaney & Huselid, 1996).…”
Section: Research Instrumentsmentioning
confidence: 99%
“…A research is conducted as a quantitative research due to the application of a more quantitative design for well-known subjects (Ward et al, 2002). Furthermore the research was conducted in a natural environment of the organization thus the interference could be minimized by the researcher.…”
Section: Methodsmentioning
confidence: 99%